2015
DOI: 10.1136/bmjopen-2015-007885
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between education levels and booster counselling sessions on smoking cessation among Chinese smokers

Abstract: ObjectivesAlthough various effective interventions are available to help individuals quit smoking, the effect of educational levels on cessation rates has rarely been studied, and of the few intervention studies on this topic, the results have been conflicting.Design and settingFrom October 2008 to August 2013, a partly retrospective non-randomised study was conducted in a smoking cessation clinic of a large general hospital in Beijing, China.ParticipantsIn total, 547 Chinese smokers who sought treatment were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
3
2
0
Order By: Relevance
“…Young health professionals in China are provided universal education on the harms of smoking and tend to have positive attitudes towards smoking bans (45), both of which may account for their lower smoking rates. Perhaps for the same reasons, those with higher levels of education have been more successful in quitting smoking than those with lower levels of education (46).Previous studies found that being divorced or separated was more likely to be associated with lower life satisfaction and predicted a higher risk of smoking than being married (29,47). In addition, we found significant regional differences in smoking, with higher rates in West and Northeast China than those in East China.…”
Section: Discussionsupporting
confidence: 51%
“…Young health professionals in China are provided universal education on the harms of smoking and tend to have positive attitudes towards smoking bans (45), both of which may account for their lower smoking rates. Perhaps for the same reasons, those with higher levels of education have been more successful in quitting smoking than those with lower levels of education (46).Previous studies found that being divorced or separated was more likely to be associated with lower life satisfaction and predicted a higher risk of smoking than being married (29,47). In addition, we found significant regional differences in smoking, with higher rates in West and Northeast China than those in East China.…”
Section: Discussionsupporting
confidence: 51%
“…The finding that a lower educational level (no college experience) was associated with a higher likelihood of biochemically confirmed abstinence has also been reported elsewhere [ 60 , 61 ]. However, reports on the association between higher educational levels and successful cessation are more common [ 19 , 57 , 58 , 62 - 64 ].…”
Section: Discussionsupporting
confidence: 76%
“…The finding that a lower educational level (no college experience) was associated with a higher likelihood of biochemically confirmed abstinence has also been reported elsewhere [60,61]. However, reports on the association between higher educational levels and successful cessation are more common [19,57,58,[62][63][64].…”
Section: Predictorssupporting
confidence: 60%